ANALISIS KEMAMPUAN GURU DALAM PELAKSANAAN PEMBELAJARAN SENI BUDAYA BIDANG SENI RUPA BERDASARKAN KURIKULUM 2013 DI SMPN 31 PADANG - Syahrul Ramadhan; Suib Awrus; Wisdiarman Wisdiarman (Serupa The Journal of Art Education, 2020)
This research is a teacher of Art and Culture in Fine Art at SMPN 31 Padang amounting to 7 people. This study aims to obtain an overview of the Analysis of the Teacher Ability in the Implementation of Cultural Art Learning in the Field of Fine Arts based on the 2013 Curriculum at SMPN 31 Padang. This type of research is quantitative descriptive in the form of ex post facto. Research data were collected using an assessment instrument (Assessment format). Data were then analyzed using percentage techniques. The research findings show that the implementation of art and culture learning in the field of fine arts based o the 2013 curriculum at SMPN 31 Padang has been categorized as good, but there are still no good categories of preparation of learning implementation plans from aspects of determining learning methods, selecting learning resources and planninng assessments in the good enough categories, while in the aspect of choosing media and learning materials in the category is not good. Based on the research findings above, it can be concluded that the implementation of art and culture learning in the field of Fine Art based on the 2013 curriculum at SMPN 31 Padang as a whole can be categorized as good, but has not yet reached the maximum or very good category.Kata Kunci: Kemampuan Guru dan Kurikulum 2013